PERAN MEDIA DIGITAL DALAM PEMBELAJARAN FIQIH DI MAN 2 AGAM - Mardeti; Maghfirani Najla Azwar; Gema Hista Medika (SURAU : Journal of Islamic Education, 2026)
The rapid development of information and communication technology has encouraged the integration of digital media into educational practices to enhance learning effectiveness. This study aims to analyze the role of digital media in improving the effectiveness of Fiqh learning at MAN 2 Agam. A descriptive qualitative approach was employed, involving 22 informants consisting of two Fiqh teachers and 20 eleventh-grade students. Data were collected through observations, interviews, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that digital media enhances students' learning interest, participation, and understanding of Fiqh by presenting learning materials in more engaging and diverse formats. In addition, digital media fosters better interaction between teachers and students throughout the learning process. However, its implementation is constrained by limited internet access, differences in digital literacy, and the suboptimal utilization of digital media in certain learning activities. The study concludes that digital media plays a significant role in improving the effectiveness of Fiqh learning and provides practical insights for teachers and schools to optimize technology-based learning.